Measuring Time Use of Older Couples: Lessons from the Panel Study of Income Dynamics - Freedman, Vicki A. (2013)
Time diaries are a well established method for providing population estimates of the amount of time and types of activities respondents carry out over the course of a full day. This paper focuses on a computer assisted telephone application developed to collect multiple, same-day 24-hour diaries from older couples who participated in the 2009 Panel Study of Income Dynamics (PSID). We present selected findings from developmental and field activities, highlighting methods for three diary enhancements: 1) implementation of a multiple, same-day diary design; 2) minimizing erroneous reporting of sequential activities as simultaneous; and 3) tailoring activity descriptors (or “follow-up” questions) that depend on a pre-coded activity value. A final section discusses limitations and implications for future time diary efforts.